Research on the Cattle Farm Endowments from the Climate Change Adapting Perspective - Steliana Rodino; Rodica Chetroiu; Diana Maria Ilie; Ancuța Marin; Vili Dragomir; Alexandra Marina Manolache; Petruța Antoneta Turek-Rahoveanu (Agriculture)
All agricultural sectors are under the influence of environmental factors, which act alongside the flow of activities. In the context of efforts to adapt to the effects of climate change, the purpose of this work is to evaluate the level of endowment of cattle farms with equipment and facilities involved in ensuring an adequate microclimate, in the efficient management and administration of feed and water for animals. This research is based on the processing of data from 83 cattle farms in Romania, of different sizes and located in different landforms, collected through a quantitative survey, through a questionnaire. This paper indicates that the existing level of these types of facilities is insufficient and highlights the importance of investments in equipment necessary to adapt to the effects of climate change, especially for smaller farms, but also for large farms. These types of investment refer to technologies for air cooling, microclimate control, feed management, and automation. This paper highlights the need to increase the technological level in Romanian cattle farms, to adapt to climate change challenges. The promotion of appropriate technologies must be included in an integrated strategy for the equipping and modernization of cattle farms, for an effective diminution of climate risks. This means adopting a systemic approach that includes investments in infrastructure, innovation, and support for farmers.